Regulatory Capture by Sophistication - Hendrik Hakenes; Isabel Schnabel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
One explanation for the poor performance of regulation in the recent financial crisis is that regulators had been captured by the financial sector. We present a micro-founded model with rational agents in which banks may capture regulators due to their high degree of sophistication. Banks can search for arguments of differing complexity against regulation. Finding such arguments is more difficult for a bad bank, which the regulator wants to regulate more strictly. However, the more sophisticated a bank is, the more easily it can produce an argument that a regulator may not understand. Career concerns prevent the regulator from admitting this, hence he rubber-stamps even bad banks, which leads to inefficiently low levels of regulation. Bank sophistication leads to capture, and thus to worse regulatory decisions.
Keywords: G21; G28; L51; 330